2011
DOI: 10.1371/journal.pone.0025258
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and Changes in Registered Data and Reporting Bias of Randomized Controlled Trials in ICMJE Journals after Trial Registration Policy

Abstract: ObjectiveWe assessed the adequacy of randomized controlled trial (RCT) registration, changes to registration data and reporting completeness for articles in ICMJE journals during 2.5 years after registration requirement policy.MethodsFor a set of 149 reports of 152 RCTs with ClinicalTrials.gov registration number, published from September 2005 to April 2008, we evaluated the completeness of 9 items from WHO 20-item Minimum Data Set relevant for assessing trial quality. We also assessed changes to the registrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 39 publications
(42 reference statements)
6
90
2
Order By: Relevance
“…A P value of less than 0.05 was considered significant. 9,15 The lead and corresponding author, subject of the trial, and dates of commencement and completion of the trial were also noted. The source of funding of the trial was also extracted.…”
Section: Methodsmentioning
confidence: 99%
“…A P value of less than 0.05 was considered significant. 9,15 The lead and corresponding author, subject of the trial, and dates of commencement and completion of the trial were also noted. The source of funding of the trial was also extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Many registry entries are incomplete, out-of-date, or have not been updated recently 13 As of October 2016, the recruitment status of nearly 21,000 ClinicalTrials.gov records is “Unknown” (i.e., listed as “Recruiting,” “Not yet recruiting,” or “Active, not recruiting,” but not confirmed within at 2 years)…”
Section: Tablementioning
confidence: 99%
“…Huic et al looked at a different sample of 152 RCTs and found that the registry entries commonly failed to provide adequate description of key secondary outcomes (44.1% of RCTs) or primary outcomes (38.8% of RCTs). 63 Prevalence of differences between the registry entry and the journal publication varied depending on the data field of interest, ranging from 13.8% to 77.6%. However, in a more recent study, Norris et al reported a catalog of problems during their attempts to evaluate selective outcome or analysis reporting through comparison of registry entries and journal reports of trials that had been included in systematic reviews of effectiveness.…”
mentioning
confidence: 99%